Revisiting the authority of âalidjma almadrakiâ (idjma with known origins) - Ã˜Â´Ã˜Â§ÃšÂ©Ã˜Â±Ã›ÂŒ, Ã˜Â¨Ã™Â„Ã˜Â§Ã™Â„ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Non-authority of âalidjma almadrakiâ (idjma with known origins) is a topic frequently raised in the Usulisâ contemporary literature. In this paper, the authority of âalidjma almadrakiâ has been studied through revisiting this idjma since the introduction of idjma in general by Shia scholars up to the present. The results of this study show that based on all foundations raised to prove the authority of idjma (hiss (intuition), lutf (benign), hads (surmise), etc.), one may assert that such idjma has authority or at least plays an important role in determining the minor premise of apparent meaning of sharia evidences and compensating for imperfection of their indication. Therefore, one may not consider idjma invalid and exclude it in deducting sharia percepts merely because its origins are known.